Solanum tuberosum Leaf Extract Templated Synthesis of Co3O4 Nanoparticles for Electrochemical Sensor and Antibacterial Applications. (8th March 2022) - Bekele, Eneyew Tilahun; Murthy, H. C. Ananda; Muniswamy, Dhanalakshmi; Lemenh, Yeshaneh Adimasu; Shume, Minale Shegaw; Tadesse Ayanie, Gezahegn; Kumar, Avvaru Praveen; Ravikumar, C. R.; Balachandran, R.; Roy, Arpita
Abstract : Green synthesis of metal oxide nanoparticles (NPs) is a viable alternative methodology because of cost-effective and availability of environmentally friendly templates for desired application, which has attracted the attention of researchers in recent years. In the present study, Co3 O4 NPs were synthesized in various volume ratios in the presence of Solanum tuberosum leaf extract as a template. The synthesized Co3 O4 NPs were characterized by X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), surface area electron diffraction (SAED), UV-Vis diffuse reflectance spectroscopy (UV-DRS), and Fourier transform infrared (FTIR) spectroscopy. XRD analysis found that the average crystalline sizes for the 1 : 2, 1 : 1, and 2 : 1 volume ratios was 25.83, 21.05, and 27.98 nm, respectively. SEM-EDX and TEM analyses suggest that the green-synthesized Co3 O4 NPs are spherical in shape without the presence of impurities. The band gap E g values of the 1 : 2, 1 : 1, and 2 : 1 volume ratios of Co3 O4 NPs were found to be 1.83, 1.77, and 2.19 eV, respectively. FTIR analysis confirmed the presence of various bioactive ingredients within the leaf extract of Solanum tuberosum . Co3 O4 NPs-modified electrodes showed better sensing capability towards ascorbic acid and citric acid due to enhanced electron transfer kinetics. Among three volume ratios (1 : 2, 1 : 1, and 2 : 1) of Co3 O4 nanoelectrodes, 1 : 1 and 2 : 1 were identified as the best performing nanoelectrodes. This is possibly due to the high catalytic behavior and the more homogenized surface structure. Co3 O4 (1 : 2) nanodrug showed the enhanced antibacterial activity (16 mm) towards S. aureus which is attributed to the formation of enhanced reactive oxygen species (ROS).